SutureHap: Use of a physics engine to enable force feedback generation on deformable surfaces simulations. (18th January 2018) - Ricardez, Eusebio; Noguez, Julieta; Neri, Luis; Escobar-Castillejos, David; Munoz, Lourdes
Haptic devices have been highly valued in virtual training environments in the medical field. Nevertheless, the principal challenges to develop these environments are the complexity to model the virtual elements and to provide proper haptic feedback during tasks. In this study, it was decided to take advantage of NVIDIA PhysX physics engine to produce a fast and effortless process in the creation of a virtual training environment for suturing tasks. Although PhysX correctly deploys collisions between solid and deformable objects in the graphical environment, it does not send this information to the developers environment to provide haptic rendering. Therefore, in this article, a "simplified method" was proposed to facilitate the detection of collisions between rigid and deformable bodies. This simplified method allows the calculation of haptic feedback to be displayed, and it avoids complexity and high computational costs. Additionally, an architecture to facilitate the integration of haptic devices was designed. The study case proposed in this work was the development of an application to perform a suturing task, SutureHap. The system was tested by volunteers from different areas and senior medical students. The latter pointed out that SutureHap is very promising, and it could be a useful tool to develop surgical skills. Finally, participants agreed that the use of the elements in the environment is reasonably intuitive, and all of them stated that they would recommend the simulator.